Lithium-rich manganese-based positive electrode and preparation method and application thereof
By using polysilazane with a specific structure as a binder in the lithium-rich manganese-based oxide positive electrode material, the problem of poor battery life caused by manganese dissolution behavior during the cycle is solved, and higher cycle stability and thermal stability are achieved.
Patent Information
- Application Number
- CN202411714735.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-04-18
AI Technical Summary
In the prior art, the dissolution behavior of the lithium-rich manganese-based oxide (LRMO) cathode material caused by structural instability during circulation, resulting in poor battery cycle life, limiting its practicality.
Polysilazane (PSZ) with a specific structure is used as the binder, and the migration energy barrier is increased by coordinating with the transition metal element in LRMO, and the bonding ability is maintained at high temperatures, thereby inhibiting the side reaction between the positive electrode and the electrolyte.
It effectively improves the cycle life and cycle stability of the battery, improves the thermal stability and hydrophobicity of the lithium-rich manganese-based positive electrode, and extends the storage time of the electrode sheet.
Smart Images

Figure SMS_2 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion batteries, and in particular to a lithium-rich manganese-based positive electrode and a preparation method and application thereof. Background Art
[0002] Lithium-rich manganese-based oxide (LRMO) cathode material is composed of LiMO2 phase and Li2MnO3 phase, and is considered to be a material with great potential for improving cathode capacity. It has extremely high energy density (>250mAh / g) and low cost, so it has attracted more and more attention from the industry.
[0003] The manganese dissolution behavior caused by the structural instability of LRMO during long cycles is an important limiting factor affecting the practical application of LRMO cathode materials. Therefore, developing a method to stabilize LRMO during the cycle is a technical problem that the industry urgently needs to solve. + Conductive Armor-like Cathode Electrolyte Interphase via Partially Fluorinated Electrolyte Engineering) designed a new type of fluoride electrolyte to inhibit the dissolution of transition metal elements during the cycle, and proposed an armor-like cathode-electrolyte interphase model to explain the mechanism of its stable 4.9V LRMO cathode. At a voltage of 4.8V, the 9Ah-level Li||LRMO soft pack battery has 576Wh kg −1The energy density of the cathode electrolyte interphase is 250.4 mAh·g-1, and the stable cycle life is more than 38 times. The literature (In situ construction of a favorable cathode electrolyte interphase through a fluorosilane additive for high-performance Li-rich cathode materials) uses trimethoxy (3,3,3-trifluoropropyl) silane (TMTFS) as a multifunctional electrolyte additive to regulate the LRMO cathode interface, and the cycle stability is significantly improved. Under the condition of this additive, the reversible capacity of the LRMO electrode is 250.4 mAh·g-1, and the capacity retention rate after 200 cycles is still 91%. The TMTFS additive can not only form a strong, thin and dense LiF-dominated cathode electrolyte interface (CEI), but also remove harmful HF in the electrolyte and prevent the dissolution of transition metal elements. In addition, the TMTFS additive can adjust the solvation environment of lithium ions, thereby increasing the migration number of lithium ions. Although these electrolytes improve the stability of LRMO, as the cycle process proceeds, the volume change of the pole piece, side reactions, etc. will gradually destroy the CEI layer, resulting in a decrease in cycle stability. Summary of the invention
[0004] In order to overcome the technical problem of poor battery cycle life caused by the dissolution of transition metal elements generated in the LRMO pole piece during the cycle in the prior art, the present invention provides a lithium-rich manganese-based positive electrode, which includes 1-10 parts of a binder by weight, and the binder is a polysilazane having the following structure: , Wherein, R1 and R2 are respectively one of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, vinyl, allyl, methylamino, hydrogen, trifluoromethyl, and pentafluoroethyl; n≥10.
[0005] The nitrogen element on the main chain of polysilazane (PSZ) can coordinate with the transition metal elements in LRMO to increase the energy barrier for the migration of transition metal ions. The coordination bond can make polysilazane fit tightly to the surface of the main material, inhibiting the side reaction between the positive electrode main material and the electrolyte. At the same time, the high temperature resistance of polysilazane can maintain its bonding ability when the battery is heated up, and inhibit the side reaction of the positive electrode at high temperature to prevent further thermal runaway reaction. The hydrophobicity of polysilazane can also improve the moisture resistance of the pole piece and extend the shelf life of the pole piece.
[0006] The lithium-rich manganese-based positive electrode provided by the present invention adopts the polysilazane with the above structure as a binder, which effectively improves the cycle life and cycle stability of the battery, and at the same time, also improves the thermal stability and hydrophobicity of the lithium-rich manganese-based positive electrode.
[0007] In some embodiments of the present invention, R1 is selected from one of methyl and propyl; R2 is selected from one of ethyl, butyl and vinyl.
[0008] In some embodiments of the present invention, R1 is a methyl group, and R2 is selected from an ethyl group and a vinyl group.
[0009] In some embodiments of the present invention, R1 is propyl and R2 is butyl.
[0010] In some embodiments of the present invention, 70-98 parts by weight of lithium-rich manganese-based active particles are also included.
[0011] In some embodiments of the present invention, the conductive agent further comprises 0.5-20 parts by weight of at least one selected from graphite, carbon black, Ketjen black, carbon nanotubes, graphene and graphyne.
[0012] In some embodiments of the present invention, 0-10 parts of an auxiliary binder are further included by weight; preferably, the auxiliary binder is selected from at least one of styrene-ethylene butylene-styrene copolymer (SEBS), styrene butadiene rubber (SBR), polytetrafluoroethylene (PTFE), polyisobutylene (PIB), nitrile rubber (NBR), polyvinyl butyral (PVB), polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), and polyacrylonitrile (PAN).
[0013] The lithium-rich manganese-based positive electrode provided by the present invention improves the mechanical properties of the lithium-rich manganese-based positive electrode by adding an auxiliary binder and relying on the flexibility brought by the high molecular weight.
[0014] In some embodiments of the present invention, the composition comprises, by weight, 1-10 parts of a binder, 0-10 parts of an auxiliary binder, 70-98 parts of lithium-rich manganese-based active particles and 0.5-20 parts of a conductive agent, preferably with a total weight of 100 parts.
[0015] In a second aspect of the present invention, a method for preparing the lithium-rich manganese-based positive electrode is provided, comprising: (1) dispersing a formulated amount of a binder, an auxiliary binder, lithium-rich manganese-based active particles and a conductive agent in a solvent to prepare a slurry; (2) applying the slurry onto a current collector by scraping; (4) drying the current collector coated with the slurry to obtain a pole piece; (5) rolling the electrode sheet after drying; (6) The rolled electrode is die-cut to a suitable size and dried until the solvent is completely removed.
[0016] In some embodiments of the present invention, in step (1), the solvent is selected from at least one of N-methylpyrrolidone, dimethyl carbonate, diethyl carbonate, propylene carbonate, anisole, n-heptane, n-pentane, hexane, cyclohexane, n-butyl ether, ethylene glycol dimethyl ether, acetonitrile, tetrahydrofuran, methyltetrahydrofuran, ethyl acetate dimethyl sulfoxide, and dimethylformamide.
[0017] In some embodiments of the present invention, step (4) is dried in a blast oven; the blast drying temperature is 30-150° C., and the blast drying time is 2-24 h.
[0018] In some embodiments of the present invention, in step (6), the die-cut electrode piece is placed in a vacuum oven and vacuum dried at 50-200° C. until the solvent is completely removed.
[0019] According to the third aspect of the present invention, a lithium battery is provided, which adopts the lithium-rich manganese-based positive electrode. The lithium battery can be a battery cell, a battery module or a battery pack. For example, the lithium battery can be a soft pack battery, a square shell battery or a cylindrical battery. The battery is composed of LRMO pole piece / electrolyte / negative electrode, wherein the electrolyte can be a liquid / solid / semi-solid electrolyte, and the negative electrode can be one or more of graphite, hard carbon, soft carbon, silicon, silicon carbon, silicon dioxide, and lithium metal.
[0020] According to a fourth aspect of the present invention, there is provided an electrical device, which uses the lithium battery. The lithium battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.
[0021] In some embodiments, the electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the electric device's requirements for high power and high energy density of the battery, a battery pack or a battery module may be used.
[0022] As another example, the power-consuming device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a battery cell may be used as a power source.
[0023] The beneficial effects of the present invention are as follows: 1. There are hydrogen bond interactions between polysilazane molecules, which can effectively improve the bonding strength of the adhesive.
[0024] 2. Polysilazane has good heat resistance and can maintain structural integrity and mechanical properties at high temperatures, thereby improving the safety performance of the battery.
[0025] 3. Polysilazane has good solubility and can be well dissolved in low-polarity solvents including alkanes.
[0026] 4. Polysilazane has extremely strong hydrophobicity, which can significantly improve the moisture resistance of the electrode and extend the storage time of the electrode.
[0027] 5. Polysilazane can coordinate with transition metal elements to prevent them from dissolving and migrating to the negative electrode, thereby improving the cycle stability of the LRMO positive electrode. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0030] In the following examples, the polysilazane used has a value of n of 15; the LRMO active particles are composed of Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2, prepared by co-precipitation method.
[0031] In the following examples, the weight unit is g, and in fact 1 g = 1 part, such as 80 g of LRMO active particles and 5 g of PSZ, which means 80 parts of LRMO active particles and 5 parts of PSZ, and so on. It can also be expressed as the mass ratio of LRMO active particles to PSZ is 80:5, and so on.
[0032] In the following embodiments, the pole pieces are cut to a diameter of 14 mm and a surface density of 9 g / cm 2 , compacted density is 1.3g / cm 3 , and button cells were assembled using 1 mol / L LiPF6FEC / DMC (1:2, V / V) + 1% LiDFOB as electrolyte, celgard 2400 as separator, and lithium sheet as negative electrode for electrochemical performance testing.
[0033] Example 1 This embodiment provides a lithium-rich manganese-based positive electrode, which is composed of: 80g of LRMO active particles, 5g of PSZ (R1 and R2 are methyl and ethyl, respectively, and n is 15), 5g of PVDF and 10g of carbon black.
[0034] This embodiment also provides a method for preparing the lithium-rich manganese-based positive electrode, comprising: (1) In a glove box, LRMO, PSZ (R1 and R2 are methyl and ethyl, respectively, and n is 15), PVDF, carbon black, and N-methylpyrrolidone were mixed and added to a homogenizer to prepare a slurry; (2) Fix the aluminum foil horizontally on the coating platform; (3) Use a scraper of a certain thickness to scrape the slurry onto the aluminum foil; (4) Transfer the electrode to a forced air oven and dry at 50°C for 8 h; (5) Rolling the electrode after drying; (6) Die-cut the electrode into a suitable size and place it in a vacuum oven at 100°C for vacuum drying until the solvent is completely removed.
[0035] Example 2 This embodiment provides a lithium-rich manganese-based positive electrode, which is composed of: 80g of LRMO active particles, 5g of PSZ (R1 and R2 are propyl and butyl, respectively, and n is 15), 5g of PTFE and 10g of graphene.
[0036] In this embodiment, the preparation method of the lithium-rich manganese-based positive electrode includes: (1) In a glove box, LRMO, PSZ (R1 and R2 are propyl and butyl, respectively, and n is 15), PTFE, graphene, and dimethyl sulfoxide were mixed and added into a homogenizer to prepare a slurry; (2) Fix the aluminum foil horizontally on the coating platform; (3) Use a scraper of a certain thickness to scrape the slurry onto the aluminum foil; (4) Transfer the electrode to a forced air oven and dry at 60°C for 10 h; (5) Rolling the electrode after drying; (6) Die-cut the electrode into a suitable size and place it in a vacuum oven at 100°C for vacuum drying until the solvent is completely removed.
[0037] Example 3 This embodiment provides a lithium-rich manganese-based positive electrode, which is composed of: 80g of LRMO active particles, 3g of PSZ (R1 and R2 are methyl and ethyl, respectively, and n is 15), 7g of NBR and 10g of graphene.
[0038] In this embodiment, the preparation method of the lithium-rich manganese-based positive electrode includes: (1) In a glove box, LRMO, PSZ (R1 and R2 are methyl and ethyl, respectively, and n is 15), NBR, graphene, dimethyl sulfoxide and dimethyl carbonate in a volume ratio of 7:3 were mixed and added into a homogenizer to prepare a slurry; (2) Fix the aluminum foil horizontally on the coating platform; (3) Use a scraper of a certain thickness to scrape the slurry onto the aluminum foil; (4) Transfer the electrode to a forced air oven and dry at 70°C for 8 h; (5) Rolling the electrode after drying; (6) Die-cut the electrode into a suitable size and place it in a vacuum oven at 100°C for vacuum drying until the solvent is completely removed.
[0039] Example 4 This embodiment provides a lithium-rich manganese-based positive electrode, which is composed of: 80g of LRMO active particles, 3g of PSZ (R1 and R2 are methyl and vinyl, respectively, and n is 15), 7g of PTFE and 10g of carbon nanotubes.
[0040] In this embodiment, the preparation method of the lithium-rich manganese-based positive electrode includes: (1) In a glove box, LRMO, PSZ (R1 and R2 are methyl and vinyl, respectively, and n is 15), PTFE, carbon nanotubes, and N,N-dimethylformamide were mixed and added into a homogenizer to prepare a slurry; (2) Fix the aluminum foil horizontally on the coating platform; (3) Use a scraper of a certain thickness to scrape the slurry onto the aluminum foil; (4) Transfer the electrode to a forced air oven and dry at 80°C for 4 h; (5) Rolling the electrode after drying; (6) Die-cut the electrode into a suitable size and place it in a vacuum oven at 100°C for vacuum drying until the solvent is completely removed.
[0041] Comparative Example 1 In this comparative example, a lithium-rich manganese-based positive electrode is provided, which is composed of 80 g of LRMO, 10 g of PVDF and 10 g of carbon black.
[0042] In this comparative example, the preparation method of the lithium-rich manganese-based positive electrode includes: (1) In a glove box, LRMO, PVDF, carbon black and N-methylpyrrolidone were mixed and added into a homogenizer to prepare a slurry; (2) Fix the aluminum foil horizontally on the coating platform; (3) Use a scraper of a certain thickness to scrape the slurry onto the aluminum foil; (4) Transfer the electrode to a forced air oven and dry at 50°C for 8 h; (5) Rolling the electrode after drying; (6) Die-cut the electrode into a suitable size and place it in a vacuum oven at 100°C for vacuum drying until the solvent is completely removed.
[0043] Test example Test object: lithium-rich manganese-based positive electrode obtained in each embodiment and comparative example Test method: Use a contact angle analyzer to measure the water contact angle of the prepared lithium-rich manganese-based positive electrode to characterize its hydrophobicity. The larger the contact angle, the better the hydrophobicity, and the better the hydrophobicity, the better the water resistance. The lithium-rich manganese-based positive electrode obtained in each embodiment and comparative example was activated at 0.1C for the first cycle, and then a cycle test was performed at a current of 0.5C, with a voltage range of 2~4.8V.
[0044] Test results: The results are shown in Table 1.
[0045] Table 1
[0046] Note: " / " in the table means no addition It can be seen from Table 1 that, relative to Comparative Example 1, the battery assembled with the obtained lithium-rich manganese-based positive electrode in the embodiment of the present invention has a higher capacity retention rate after 200 cycles at 0.5C, which is increased by 10%-21%. At the same time, the water resistance of the electrode piece and the thermal stability of the assembled battery are significantly improved, indicating that the use of the lithium-rich manganese-based positive electrode of the present invention can significantly improve the dissolution of transition metal elements generated by the LRMO electrode piece during the cycle process, thereby improving the battery life and cycle stability.
[0047] Comparing Example 1 and Comparative Example 1, under the same other conditions, the only difference is PSZ, the capacity retention rate after 200 cycles at 0.5C is increased by 21%, the water resistance is increased by 158%, and the thermal stability is increased by 37%. These results show that the use of PSZ as a binder can significantly improve the dissolution of transition metal elements produced by the LRMO pole piece during the cycle, thereby improving the battery life and cycle stability. At the same time, the addition of PSZ makes the pole piece more resistant to storage and less prone to thermal runaway.
[0048] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium-rich manganese-based positive electrode, characterized in that: The invention comprises 1-10 parts of a binder by weight, wherein the binder is a polysilazane having the following structure: , Wherein, R1 and R2 are respectively one of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, vinyl, allyl, methylamino, hydrogen atom, trifluoromethyl, and pentafluoroethyl; n≥10。 2. The lithium-rich manganese-based positive electrode according to claim 1, characterized in that: R1 is selected from one of methyl and propyl; R2 is selected from one of ethyl, butyl and vinyl; And / or, R1 is methyl, and R2 is selected from one of ethyl and vinyl; And / or, R1 is propyl and R2 is butyl.
3. The lithium-rich manganese-based positive electrode according to claim 1 or 2, characterized in that: By weight, the invention also includes 70-98 parts of lithium-rich manganese-based active particles.
4. The lithium-rich manganese-based positive electrode according to any one of claims 1 to 3, characterized in that: By weight, it also includes 0.5-20 parts of a conductive agent; Preferably, the conductive agent is selected from at least one of graphite, carbon black, Ketjen black, carbon nanotubes, graphene and graphyne.
5. The lithium-rich manganese-based positive electrode according to any one of claims 1 to 4, characterized in that: By weight, it also includes 0-10 parts of an auxiliary binder; preferably, the auxiliary binder is selected from at least one of styrene-ethylene butylene-styrene copolymer, styrene butadiene rubber, polytetrafluoroethylene, polyisobutylene, nitrile rubber, polyvinyl butyral, polyvinyl alcohol, polymethyl methacrylate, polyethylene terephthalate, polyvinylidene fluoride, carboxymethyl cellulose, polyacrylic acid, and polyacrylonitrile.
6. The lithium-rich manganese-based positive electrode according to any one of claims 1 to 5, characterized in that: In parts by weight, it includes 1-10 parts of a binder, 0-10 parts of an auxiliary binder, 70-98 parts of lithium-rich manganese-based active particles and 0.5-20 parts of a conductive agent, preferably with a total weight of 100 parts.
7. The method for preparing the lithium-rich manganese-based positive electrode according to any one of claims 1 to 6, characterized in that: include: (1) dispersing a formulated amount of a binder, an auxiliary binder, lithium-rich manganese-based active particles, and a conductive agent in a solvent to prepare a slurry; (2) applying the slurry onto a current collector by scraping; (4) drying the current collector coated with the slurry to obtain a pole piece; (5) rolling the electrode sheet after drying; (6) The rolled electrode is die-cut and dried until the solvent is completely removed.
8. The preparation method according to claim 7, characterized in that: In step (1), the solvent is selected from at least one of N-methylpyrrolidone, dimethyl carbonate, diethyl carbonate, propylene carbonate, anisole, n-heptane, n-pentane, hexane, cyclohexane, n-butyl ether, ethylene glycol dimethyl ether, acetonitrile, tetrahydrofuran, methyltetrahydrofuran, ethyl acetate dimethyl sulfoxide, and dimethylformamide; And / or, step (4) is dried in a blast oven; the blast drying temperature is 30-150° C., and the blast drying time is 2-24 h; And / or, in step (6), the die-cut electrode piece is placed in a vacuum oven and vacuum dried at 50-200° C. until the solvent is completely removed.
9. A lithium battery, characterized in that: A lithium-rich manganese-based positive electrode according to any one of claims 1 to 6 or a lithium-rich manganese-based positive electrode obtained by the preparation method according to claim 7 or 8 is used.
10. An electrical device, characterized in that: The lithium battery according to claim 9 is used.